Mixture of Carbon Derived from Lokta Paper and Graphite for Efficient Counter Electrodes of Dye-sensitized Solar Cells (Swarnadwar, 2025)
This study explores the potential of using a mixture of Lokta paper-based activated carbon (80%) and graphite powder (20%) as an efficient counter electrode (CE) material for dye-sensitized solar cells (DSSCs). The activated carbon was synthesized in two steps. Firstly, Lokta paper was carbonized at 400 ºC. Then the char was activated with ZnCl_2 and carbonized at 800 ºC. The activated carbon and its mixture were characterized by the techniques of X-ray diffraction (XRD) and scanning electron microscope (SEM). The XRD of the activated carbon disclosed the formation of both graphitic and amorphous forms of carbon in the sample. The SEM image of the Loktapaper-derived activated carbon explored a rough and porous surface, and the Energy dispersive X-ray spectroscopy (EDS) of the mixture detected high carbon content in the sample. The catalytic ability of the mixture of the activated carbon and graphite for the reduction of tri-iodide ions was investigated by electrochemical impedance spectroscopy (EIS) of symmetrical dummy cells. The charge transfer resistance at the mixture-electrolyte interface of the symmetrical cell was 1.59 Ω-cm^2. Hence, the mixture of the Lokta paper-based activated carbon and graphite can be an efficient and low-cost CE material alternative to expensive platinum used in DSSCs.